Geometrical and mechanical characterisation of hollow thermoplastic microspheres for syntactic foam applications. (15th October 2021) - Curd, Matthew E.; Morrison, Neil F.; Smith, Michael J.A.; Gajjar, Parmesh; Yousaf, Zeshan; Parnell, William J.
Abstract: Recently, hollow thermoplastic microspheres, have emerged as an innovative filler material for use in polymer-matrix composites. The resulting all-polymer syntactic foam takes on excellent damage tolerance properties, strong recoverability under large strains, and favourable energy dissipation characteristics. Aside from syntactic foams, thermoplastic microspheres are finding increasing usage in a variety of applications and industries. Despite this, there is an absence of statistical geometrical and mechanical data for certain classes of thermoplastic microspheres. In this work we characterise two classes of thermoplastic microsphere using X-ray computed tomography, focused ion beam and electron microscopy. We observe the spatial distribution of these microspheres within a polyurethane-matrix syntactic foam and show that the volume-weighted polydisperse shell diameters follow a normal distribution. Interestingly, polydispersity of the shell wall thickness is not observed and furthermore the wall thickness is not correlated to the shell diameter. We utilise the geometrical information obtained in analytical micromechanical techniques in the small strain regime to determine, for the first time, estimates of the Young's modulus and Poisson's ratio of the microsphere shell material itself. Our results contribute to potential future improvements in the design and fabrication of materials that employ thermoplastic microspheres, including syntactic foams.